Promoting effect of zinc on the vapor-phase hydrogenation of crotonaldehyde over copper-based catalysts - Rodrigues, E.L. (2005)
The promoting effect of zinc for the vapor-phase hydrogenation of crotonaldehyde was studied on impregnated Cu/SiO2 and Cu-ZnO/SiO 2, and on coprecipitated Cu-Al2O3 and Cu x-ZnyO2y-ZnAl2O4 catalysts. The reaction was carried out in a tubular reactor at 120°C and atmospheric pressure. Samples were characterized by temperature-programmed reduction, X-ray diffraction, transmission electronic microscopy, diffuse reflectance FTIR spectroscopy of adsorbed CO, and X-ray photoelectron spectroscopy. Cu/SiO2 and Cu-Al2O3 catalysts reduced in hydrogen either at 300 or 500°C hydrogenated preferentially the CC bond of crotonaldehyde and gave more than 90% of selectivity to butyraldehyde. In contrast, the initial butyraldehyde selectivity on Cu-ZnO/SiO2 reduced at 500°C was only about 55%, essentially because the selectivity to crotyl alcohol significantly increased on this zinc-containing sample as compared to Cu/SiO2. This selectivity enhancement for hydrogenating the CO bond on Cu-ZnO/SiO2 reduced at 500°C was explained by considering that the high-temperature hydrogen treatment forms mobile ZnOx reduced species that strongly interact with Cu0 crystallites. The resulting Cu0-ZnOx species preferentially catalyze the crotyl alcohol formation from crotonaldehyde via a dual-site reaction pathway. A similar explanation was proposed to interpret the observed enhancement of the CO hydrogenation rate on ternary Cu-Zn-Al catalysts reduced at 500°C as compared to Cu-Al2O 3. Nevertheless, the Cu0-ZnOx species were unstable on stream and the selectivity to crotyl alcohol continuously decreased with reaction time on zinc-containing samples reduced at high temperatures.